ECOSCHOOL Membangun Peran Ekonomi Hijau Melalui Program Peduli Lingkungan Kepada Siswa/i SMKN 3 Kota Serang - Adinda Umu Salmah1 (TRIDAYA: Jurnal Pengabdian kepada Masyarakat, 2025)
Ecoschool is a program that integrates environmental education and sustainable practices into the school curriculum. The program aims to build students' awareness and responsibility of SMKN 3 Serang City towards the environment, and encourage them to play an active role in building a green economy. Ecoschool has several benefits, including first increasing students' knowledge and awareness of environmental issues, second building environmentally friendly attitudes and behaviors, equipping students with skills and knowledge to build a green economy, third creating a healthier and more sustainable school environment. The Ecoschool program can also be implemented through various activities, such as environment-based learning, waste management and recycling, energy and water conservation, tree planting and greening, development of environmentally friendly products. And by implementing this Ecoschool program, we hope that students can become agents of change who play an active role in building a green economy and creating a sustainable future. The results showed that the Ecoschool environmental program succeeded in increasing students' awareness of environmental issues and encouraging environmentally friendly behavior. The program also contributes to building a green economy through energy saving, waste reduction, and sustainable use of natural resources